Treatment of invasive candidiasis in neutropenic patients: systematic review of randomized controlled treatment trials. Issue 7 (1st July 2013) - Kanji, Jamil N.; Laverdière, Michel; Rotstein, Coleman; Walsh, Thomas J.; Shah, Prakesh S.; Haider, Shariq
Abstract: Candidemia and invasive candidiasis (CIC) is associated with considerable morbidity and mortality, with a paucity of controlled data in neutropenic patients. A systematic review was conducted of available data for the treatment of CIC during neutropenia. A structured OVID search of multiple databases was performed. Data from randomized controlled trials of CIC and of empirical antifungal therapy in febrile neutropenic patients was included. A total of 17 trials randomizing 342 neutropenic patients were included. Eight of the studies compared amphotericin B (AmB) to other non-polyene antifungal agents. Pooling of results favored use of comparator compounds (odds ratio [OR] 0.73; 95% confidence interval [CI] 0.42–1.29). To strengthen our analysis, a pre-planned sensitivity analysis was also conducted. Overall, there was a non-significant benefit in favor of non-polyene compounds. Across studies, echinocandins provided the benefit of favorable outcomes with fewest side effects and toxicity.